FUNGSI ILMU KEDOKTERAN FORENSIK DALAM PENYIDIKAN PADA KASUS PENGGUGURAN KANDUNGAN (ABORSI) (Solusi, 2023)
Based on the provisions of the Criminal Code ( KUHAP),an investigator must prove whether a criminal act has really occured,in this case an illegal abortion,namely by having evidence as regulated in article 184 of the Criminal Procedure Code.In accordance with this provisions, forensic medical science,in this case a forensic doctor,in conducting research to find the cause of the Crime of illegal abortion (Abortion) in the case which caused the death of the victim, the results of the research from a forensic doctor are outlined in the certificate of the cause of the victim,s death due to an illegal abortion (abortion) in the form of a Visum Et Refertum,this is evidence for investigators to submit the case to Court.